Anodic Olefin Coupling Reactions: Elucidating Radical Cation Mechanisms and the Interplay between Cyclization and Second Oxidation Steps. Issue 9 (11th June 2021) - Medcalf, Zach; Moeller, Kevin D.
Abstract: Anodic olefin coupling reactions generate new bonds and ring skeletons through a net two electron process that reverses the polarity of a known, electron‐rich functional group. While much of the early work on the mechanism of these reactions focused on the initial oxidation and cyclization steps of the process, the second oxidation step also plays a central role in determining the success of the reaction. Evidence supporting this observation is presented, along with evidence that optimization of this second oxidation step is not enough to pull a poor cyclization to the desired product. Successful cyclization reactions require optimization of both processes. Abstract : Anodic olefin coupling reactions generate new bonds and ring systems through a net two electron process that reverses the polarity of a known, electron‐rich functional group. While much of the early work on the mechanism of these reactions focused on the initial oxidation and cyclization steps, the second oxidation also plays a key role in determining the success of the reaction. Evidence supporting this observation is presented, along with evidence that optimization of the second oxidation step is not enough to pull a poor cyclization to product. Successful cyclizations require optimization of both processes.